Correlated evolution between climate and suites of traits along a fast–slow continuum in the radiation of Protea. Issue 3 (12th January 2018) - Mitchell, Nora; Carlson, Jane E.; Holsinger, Kent E.
Abstract: Evolutionary radiations are responsible for much of Earth's diversity, yet the causes of these radiations are often elusive. Determining the relative roles of adaptation and geographic isolation in diversification is vital to understanding the causes of any radiation, and whether a radiation may be labeled as "adaptive" or not. Across many groups of plants, trait–climate relationships suggest that traits are an important indicator of how plants adapt to different climates. In particular, analyses of plant functional traits in global databases suggest that there is an "economics spectrum" along which combinations of functional traits covary along a fast–slow continuum. We examine evolutionary associations among traits and between trait and climate variables on a strongly supported phylogeny in the iconic plant genus Protea to identify correlated evolution of functional traits and the climatic‐niches that species occupy. Results indicate that trait diversification in Protea has climate associations along two axes of variation: correlated evolution of plant size with temperature and leaf investment with rainfall. Evidence suggests that traits and climatic‐niches evolve in similar ways, although some of these associations are inconsistent with global patterns on a broader phylogenetic scale. When combined with previous experimental work suggesting that trait–climate associations are adaptive in Protea, the results presented here suggest that trait diversification in this radiation is adaptive. Abstract : Trait‐climate associations are often indicators for the role of adaptation of plants to the abiotic environments which they occupy. The morphologically diverse and species‐rich genus Protea is an iconic plant radiation centered in the climatically heterogeneous Cape Floristic Region. Examination of present day and evolutionary associations between traits and climate variables on a strongly supported phylogeny indicates that diversification in Protea has correlated evolution along two distinct axes of variation, with correlated evolution of plant size with temperature and leaf investment with rainfall.